Potret Masyarakat Jakarta Dalam Membangun Identitas Budaya Pada Lingkup Harmoni Kebangsaan - Untung Suhardi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
Culture a territory have identity distinguish to each other. But a lot of the imposition culture is finally native culture from certain regions missing. The state of this is what in the context of history Jakarta people do not understand history truth about where their culture. Basic thought in this writing is the identity of the culture of society Jakarta and its effort to realize community tolerance in the scope of diversity. This writing using analysis qualitative phenomenologist approach. This research result in a finding of their national identity impossible destroyed just because of differences of religion party certain. On a pearl of sphere wisdom local that the Jakarta formed because of tradition an ancestor about which was already carried out in hereditary. Hence, cultural identity people still interweave tradition and culture-based tolerance and togetherness. The value of this tolerance going to come up with that there were attempts to realizing the national anthem of the using constructive dialogue, known corrupt tolerance, start applying the standards values intercultural be selective and development knowledge and technology a limited impact on the. Values this is what within the scope of globalization are to be sustained especially to the younger generation.